Well-known symptoms, new disease - a case of SARS-CoV-2 infection in an eight-year-old boy - Kinga Węglewska; Marta Józwik; Katarzyna Krawiranda; Natalia Krysiak (Termedia Publishing House, 2022)
Paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 infection (PIMS-TS) is a new disease in children, connected with the COVID-19 pandemic. The main cause of this disease is dysregulation of the immune homeostasis. We report the first case of PIMS-TS in the Polish Mother's Memorial Hospital Research Institute in Lodz. Many non-specific symptoms presented by the patient were the cause of the primary care physician's therapeutic failure, which resulted in the boy being transferred to the district hospital and then to the institute in Lodz. During the complex diagnostic process anti-SARS-CoV-2 antibodies in the IgM and IgG classes were detected. The initial diagnosis of PIMS-TS was made, and treatment with immunoglobulins and acetylsalicylic acid was initiated. The patient's condition improved the following day. The aim of this report is to emphasize that typical symptoms do not always determine known disease entities, and to point out the need to constantly improve one's knowledge.